Sociological view of food security - Koptayeva, G. P.; Syzdykov, B. Sh.; Turdalieva, U. N.; Shalbaeva, A. R.; Aimaganbetova О. Kh. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2020)
Abstract. One of the most important socio-economic tasks of a society is to create decent living conditions for its citizens, primarily by satisfying a person’s urgent need for food according to rational nutritional standards, in order to maintain public health and regulate demographic processes in the country, as well as create conditions for the reproduction of future generations. The problem of ensuring food security of the population and food independence of the state is multilevel and multidimensional in itself. This problem affects the whole range of socio-economic aspects, as well as many other points – which determines the relevance of the problem. The basis of ensuring food security of the population and food independence of the state is the developed food economic system of the country. The level of providing the population with basic domestic food products depends on its actual condition, effective use and building up of its production and economic potential. The imported food consumed directly affects the food dependence of the state; moreover, an increase in imports negatively affects the state of the country’s food economic system, restraining its development. Achieving a decent level of nutrition according to rational standards, high-quality and safe food products by all sectors of the population is the basis of the vital activity of Kazakhstan citizens citizens and is a process of implementing urgent and urgent tasks, the solution of which depends on the real participation of the entire vertical of the executive and legislative branches, business, the scientific community and society as a whole. The need for a sociological approach is caused by the interdependence of the social component of providing the population with food and the real need for the development of the food economic system of Kazakhstan. Key words: food security, socio-economic aspect, efficiency, nutrition, need.